Interest Rate Policy Of Selected Central Banks In Central And Eastern Europe - Grabia, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2015)
The aim of this article is to present and evaluate interest rate policies of three selected central banks in Central and Eastern Europe (Poland, the Czech Republic, and Hungary) from 2001 to 2013. The study consists of an introduction (Section 1) and three main parts. The introduction contains a theoretical description of the role of interest rate policy, the dilemmas connected with it, as well as an analysis of the strategies and goals of monetary policies of the National Bank of Poland (NBP), the Czech National Bank (CzNB), and the National Bank of Hungary (NBH) in the context of existing legal and institutional conditions. In turn, the first empirical part (Section 2) examines how the analysed central banks responded to changes in inflation, unemployment, and economic growth rates. The tools of the analysis are the nominal and real interest rates of those banks. The subsequent research part (Section 3) attempts to evaluate the degree of the contractionary nature of interest rate policies in specific countries in the context of the Taylor rule. The text ends with a summary (Section 4) encompassing concise conclusions drawn from the earlier analyses.